MASCULINITY, ILL HEALTH, HEALTH HELP-SEEKING BEHAVIOR AND HEALTH MAINTENANCE OF DIABETIC MALE PATIENTS: PRELIMINARY FINDINGS FROM BRUNEI DARUSSALAM - Deeni Rudita Idris; Nur Shazwana Hassan; Norashikin Sofian (Belitung Raya Foundation, Indonesia, 2019)
Background: Literature revealed that men tends to use healthcare services much lesser and visit much later, resulting in poor health outcomes. This is often regarded as a way of exhibiting masculinity. In Brunei, there is an increasing number of mortality resulting from the complication of diabetes mellitus, a non-communicable disease, which arguably can be prevented. Objectives: To explore their health-help seeking behavior and health maintenance pattern of male diabetic patients in Brunei. Methods: Qualitative research guided by phenomenology research design. COREQ Checklist was used to prepare the report of this study. Individual semi-structured interview on eleven men were conducted from February to November 2018. Interviews were audio-recorded, transcribed and analyzed thematically. Results: Three themes were developed: “Maintaining health to enable the performance of masculine roles”, “Men delay seeking healthcare services”, and “Maintaining control and self reliance in looking after own sick body”. Conclusion: Health is perceived as important - it enables men to perform their ‘masculine responsibilities’. When men are in ill-health and realized how this could jeopardize their masculine roles, they would actively involve in taking care of their own body. This suggested how masculinity is in fact context –dependent. Level of knowledge and experiences with healthcare services and treatments also influenced men decision in health-help. Despite evidence that suggests how men often decline involvement with health promoting activities and delay seeking health from healthcare professionals, it was found that being able to continue supporting their family act as a legitimate reason for them to access healthcare services.